Code-Switching and Identity on the Blogs: An Analysis of Taglish in Computer Mediated Communication - Smedley, Frank (Auckland University of Technology, 2006)
This study analyses the code-switching variety Taglish (Tagalog-English) in personal weblogs written by Filipino bloggers.The main research questions are set forth in chapter one: why do writers of weblogs code-switch in contexts where there is no specific addressee and hence no turn taking, and why is 'this' particular language chosen at 'this' juncture in the weblog narrative?Chapter two gives an overview of relevant code-switching theory and research, and focuses especially on the sociolinguistic dimensions. In particular, the markedness model of Myers-Scotton is reviewed with respect to the notion of code-switching itself as an unmarked choice. This sets the stage for introducing Taglish as a normal and unmarked phenomenon for many Filipinos.Chapter three presents the socio-political and linguistic background in the Philippines. This give a backdrop for a focus on the evolution and status of Taglish.The problems associated with the presentation of self in Computer Mediated Communication (CMC) are examined in Chapter four and then the unique characteristics of weblogs are explored with respect to their purpose and genre.Chapter five looks at the design and methodology employed and emphasises the qualitative nature of the research and the sampling method as purposive. The main corpus of 25 extracts were analysed using frameworks which bring important perspectives to bear on the use of code-switching in the construction and negotiation of identity. These frameworks are: the referee design dimension of Bell's audience design model with its emphasis on initiative style shifts to project different identities; discursive psychology which highlights the use of language to position self and others; and narrative psychology with its stress on people's use of narrative to seek coherence of self and life-experience. These frameworks are combined with Bakhtinian notions of polyphony, dialogism and heteroglossia.Chapter six gives the detailed results of the analysis of seven weblogs which typify the findings of the corpus. Code-switching on these weblogs highlights the creative end of language use. However, it is a creativity tempered by the realities of Bakhtinian heteroglossia. The heteroglossic nature of the code-switching, in seemingly monological texts, is implicated in how the bloggers negotiate and construct social identities by positioning themselves and others in the ongoing narrative flow. In that the code-switching is extremely plentiful in this non-oral environment, it poses a serious challenge to the attempts by some conversational analysts (e.g., Li, 2005) to claim that code-switching can only really be explicated in terms of the systematics of an interaction taking place. The research seeks to stay within the spirit of CA by suggesting that even in a seemingly monologic form, interaction may be reconceived as heteroglossia covertly present in all language and overtly manifest in switching. Thus switching is not merely a product of how speakers attend to the orderly production of conversation, but also a product of how they attend to the inherent heteroglossic nature of language and exploit their linguistic repertoire maximally to make their communication as effective as possible, and to construct and negotiate multiple identities.
Keywords: Blogs; Tagalog language; Code switching (Linguistics); Foreign Languages